2008
DOI: 10.3201/eid1408.080100
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Molecular Characterization of Banna Virus from Mosquitoes, Vietnam

Abstract: We isolated and characterized a Banna virus from mosquitoes in Vietnam; 5 strains were isolated from fi eld-caught mosquitoes at various locations; Banna virus was previously isolated from encephalitis patients in Yunnan, China, in 1987. Together, these fi ndings suggest widespread distribution of this virus throughout Southeast Asia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 8 publications
0
25
0
Order By: Relevance
“…dorsalis, Aedes vagus, and An. sinensis in Yunnan, Gansu, Beijing, Shanxi, and Liaoning provinces in China (Tao and Chen 2005, Sun et al 2009, Liu et al 2010) as well as in Indonesia (Attoui et al 2005) and Vietnam (Nabeshima et al 2008 (Xu et al 1990). However, this speculation requires further investigation.…”
Section: Discussionmentioning
confidence: 98%
“…dorsalis, Aedes vagus, and An. sinensis in Yunnan, Gansu, Beijing, Shanxi, and Liaoning provinces in China (Tao and Chen 2005, Sun et al 2009, Liu et al 2010) as well as in Indonesia (Attoui et al 2005) and Vietnam (Nabeshima et al 2008 (Xu et al 1990). However, this speculation requires further investigation.…”
Section: Discussionmentioning
confidence: 98%
“…vagus) (Liu et al, 2010a). Additionally, BAV has been isolated from mosquitoes collected in Indonesia (Brown et al, 1993), Vietnam (Nabeshima et al, 2008), and many provinces of China (from the southern Yunnan…”
Section: Discussionmentioning
confidence: 99%
“…Since then, BAV has been isolated from various mosquito specimens (Liu et al, 2010), suggesting that mosquitoes are the natural vector for BAV. To date, BAV has been isolated from mosquito specimens collected in Indonesia (Brown et al, 1993), Vietnam (Nabeshima et al, 2008), South Korea (Kim et al, 2016), as well as from many subtropical or temperate provinces of China (Gansu, Shanxi, Inner Mongolia, Liaoning, Beijing, and Yunnan) (Liu et al, 2010a;Liu et al, 2010b;Liu et al, 2011). Moreover, it was recently reported that BAV has been isolated in Hungary, which is in the northern, more temperate zone of Europe (Reuter et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…There are three species of seadornaviruses: Banna virus (BAV), Kadiporo virus (KDV) and LNV. BAV has been isolated from encephalitic humans (26, 27), pigs, cattle (28), and mosquitoes in China (29, 30), Indonesia (31) and Vietnam (32). Serosurveys of patients with encephalitis across China revealed a BAV seroprevalence of about 10% (33).…”
Section: Discussionmentioning
confidence: 99%